Is the Mattis Dementia Rating Scale appropriate to detect Mild Cognitive Impairment? - Belaus, Anabel (2015)
Some studies have tried to assess the Mattis Dementia Rating Scale (MDRS) capability to detect incipient dementia or Mild Cognitive Impairment (MCI), but the results are not clear. The aim of this research was to evaluate the sensitivity and specificity of the MDRS, and to localize the optimal cutoff score for MCI. Methodology. A neuropsychological battery that included the MDRS was administered to 60 older adults of both genders (Mean age=68.38, SD=6.80) in Córdoba, Argentina, who were then classified as “Control” (34 cases) or “MCI” (26 cases) according to performance in the neuropsychological evaluation, excluding the MDRS. The criteria used were those stated by the Sociedad Española de Neurología. We performed mean comparisons in order to evaluate if the MDRS was able to detect the group differences. Then, a logistic regression with the MDRS total score as the predictor variable and the group as the criterion variable was performed to determine the cutoff score. Results. Even though the mean comparisons showed a significant difference in the MDRS (p=.004), the diagnostic accuracy was only 63% with a 133 points cutoff score. The sensitivity was 42% and the specificity was 79%. Conclusions. The MDRS does not seem to be a useful tool to detect MCI since it generates numerous misclassified cases. The development of more accurate tools becomes fundamental in order to detect MCI.